2021
DOI: 10.1080/14756366.2021.1900163
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological activities and docking studies of pleuromutilin derivatives with piperazinyl urea linkage

Abstract: Antibiotics resistance is becoming increasingly common, involving almost all antibiotics on the market. Diseases caused by drug resistant bacteria, such as MRSA, have high mortality and negatively affect public health. The development of new drugs would be an effective means of solving this problem. Modifications based on bioactive natural products could greatly shorten drug development time and improve success rate. Pleuromutilin, a natural product from the basidiomycete bacterial species, is a promising anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Basidiomycetes are rich sources of terpenes with extensive pharmacological activities, such as the antidepressant effect of Armillaria mellea (Zhang et al 2021a , b , c ), the anticancer and anti-inflammatory activity of Antrodia camphorata (Wang et al 2019a , b ), the antitumour and immunoregulatory effects of L. rhinocerotis , and the antitumour, anti-inflammatory and antiallergic effects of Agaricus blazei , H. erinaceus and Grifola frontosa (Lau et al 2015 ). However, genetic manipulation of basidiomycetes is known to be difficult and immature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basidiomycetes are rich sources of terpenes with extensive pharmacological activities, such as the antidepressant effect of Armillaria mellea (Zhang et al 2021a , b , c ), the anticancer and anti-inflammatory activity of Antrodia camphorata (Wang et al 2019a , b ), the antitumour and immunoregulatory effects of L. rhinocerotis , and the antitumour, anti-inflammatory and antiallergic effects of Agaricus blazei , H. erinaceus and Grifola frontosa (Lau et al 2015 ). However, genetic manipulation of basidiomycetes is known to be difficult and immature.…”
Section: Discussionmentioning
confidence: 99%
“…Basidiomycetes, particularly their sporocarps, contain abundant natural products (Tian et al 2020 ). For example, pleuromutilin, a diterpenoid natural product, shows moderate activities against gram-positive bacteria and mycoplasmas (Zhang et al 2021a , b , c ). Due to its low cytotoxicity in mammals and low environmental impact, pleuromutilin has been gradually developed into a commercial antibiotic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modification of the pleuromutilin glycolic ester, especially the presence of thioether group, has been shown to give derivatives with improved antibacterial activities [ 14 , 15 ], and thus has led to four drugs: tiamulin, valnemulin, retapamulin and lefamulin [ 16 – 20 ]. Tiamulin and valnemulin were approved as veterinary antibiotics for swine dysentery, enzootic pneumonia and chronic respiratory disease in poultry [ 16 , 17 , 21 ]. Retapamulin was for human topical skin infections [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Muhi-eldeen et al, synthesized a hybrid compound with 1,3,4-oxadiazole moiety and pyrrolidine connected with propargylic moiety showed antibacterial activity against Staphylococcus aureus and E. coli [ 14 ]. On the other hand, the coupling of piperazine with heterocyclic compounds enhanced the biological activities like anticancer [ 15 16 ], antibacterial [ 17 ], antimalarial [ 18 ], anti-inflammatory [ 19 ], and lead to a promising scaffold for the treatment of Alzheimer’s disease [ 20 ]. Our previous work showed that a combination between cholic acid and heterocyclic scaffolds improved the antibacterial property ( Figure 1 ) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%